Early Intervention Services for First Episode of Psychosis in South London and the Maudsley (SLaM): 20 Years of Care and Research for Young People - Fusar-Poli, Paolo; Lai, Serena; Di Forti, Marta; Iacoponi, Eduardo; Thornicroft, Graham; McGuire, Philip; Jauhar, Sameer (Frontiers in Psychiatry, 2020)
Introduction: Early Intervention for a first episode of Psychosis (EI) is essential to improve outcomes. There is limited research describing real-world implementation of EI services. Method: Analysis of service characteristics, outcomes (described through a retrospective 2007-2017 Electronic Health Record (EHR) cohort study) and clinical research relating to the first 20 years of implementation of EI services in South London and Maudsley (SLaM) Trust. Results: SLaM EI are standalone services serving 443050 young individuals in South-London, where (2017) incidence of psychosis (58.3 to 71.9 cases per 100000 person-years) is greater than the national average. From 2007-2017 (when the EHR was established), 1200 individuals (62.67% male, mean age 24.38 years, 88.17% single; two-thirds of non-white ethnicity) received NICE-compliant EI care. Pathways to EI services came mainly (75.26%) through inpatient (39.83%) or community (19.33%) mental health services or Accident and Emergency departments (A&E) (16%). At 6-year follow-up 34.92% of patients were still being prescribed antipsychotics. The 3-month and 6-year cumulative proportions of those receiving clozapine were 0.75% and 7.33%; those compulsorily admitted to psychiatric hospitals 26.92% and 57.25%; those admitted to physical health hospitals 6.83% and 31.17% respectively. Average 3-months and 6-year days spent in hospital were 0.82 and 1.85 respectively; mean 6-year attendance at A&E was 3.01. SLaM EI clinical research attracted £58 million grant income and numerous high-impact scientific publications. Conclusions: SLaM EI services represent one of the largest, most established services of its kind, and are a leading model for development of similar services in the UK and worldwide.